Case of the month: Buffalo chest: a case of bilateral pneumothoraces due to pleuropleural communication. Issue 6 (19th May 2006) - Hartin, D J; Kendall, R; Boyle, A A; Atkinson, P R T
Abstract : Simultaneous spontaneous bilateral pneumothoraces, the presentation of separate right and left pneumothoraces together, is a rare event. The pleural cavities in humans are separated completely and the only previous reports of pleuropleural communication have been associated with major invasive thoracic procedures, specifically mediastinal surgery. The term "buffalo chest" has been coined for the condition on the basis that the buffalo or bison has a single pleural cavity, one of the few mammals to do so. We present the case of a woman with a past history of a single right sided spontaneous pneumothorax but no major thoracic surgery, who presented to the emergency department with a second spontaneous right pneumothorax that was under tension. After thoracostomy, she was found to have bilateral pneumothoraces which resolved with a unilateral chest drain demonstrating pleuropleural communication. We believe this to be the first reported case of such a presentation in the literature. The case demonstrates an unusual emergency presentation of a rare anatomical anomaly.